Pembuktian Pemakaian Alat Penghemat Daya Listrik Di Masyarakat Dengan Uji Laboratorium - Sutan Marsus; Yessi Marniati; Andri Suryadi; Herman Yani (Jurnal Teknik Elektro, 2019)
The electric power saving devices work using the working principle of the capacitors, which reduces reactive power and improve the power factor in home installations. However, based on research conducted by the authors in the Electrical Laboratory at State Polytechnic of Sriwjaya Palembang, the power saving devices can not reduce reactive power and improve the power factor on the circuit. This is because the value of the capacitor to the appliance does not correspond to the value of the total load on the circuit to be repaired, if the capacitor value is too large, the capacitor itself would be a load on the circuit. In this experiment load used is inductive loads ( L ), such as transformator lamp, television, and fan with a total peak power of 402 Watt and 315 VAR reactive power. After doing the analysis and calculation, the rating value of the capacitor is needed to reduce reactive power and improve the power factor of 0.78 up to 0.9 and reduce the reactive power of 315 VAR  down to 191.77 was 8.1 μF.